Biofilm in methicillin sensitive and resistant Staphylococcus aureus - Yeiny Coromoto Ávila-Roo; Messaria María Ginestre-Pérez; María Castellanos-Tolosa; Franci Escobar-Velázquez; Amarilis Briceño-Peñalosa; Kutchynskaya Josefina Valero-Leal; Gresleida Coromoto Rincón-Villalobos; Johandry Rivero-Salazar (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
The formation of biofilm is a life strategy for most bacteria, since it increases the possibilities of transfer of genetic material and resistance to antibiotics, participates in cellular communication and offers protection in adverse and variable environmental conditions; what contribute to a successful colonization of the host. This research aimed to determine the capacity to produce biofilm in isolates of S. aureus. Thirty isolates (13 sensitive and 17 resistants to methicillin) were studied by assay on cell culture microplates. All strains showed adherence patterns; 24 (80%), 4 (13%) and 2 (7%) exhibited degrees of moderate, weak and strong adhesion, respectively. 77% of sensitive strains were moderately productive, 13% weak and 7% strong producers of biofilm. The resistant strains presented a moderate production (82%) and 18% a weak production. There was no association between the degree of adherence and the susceptibility to methicillin. The high rate of biofilm production in clinical strains of S. aureus, sensitive and resistant to methicillin, suggests the potential danger posed by such strains inside and outside hospital environments, given the importance that biofilms play in the development of chronic infections.